Cultural Diplomacy as a Tool in Post-Conflict Reconciliation? - Ivana Vesić (Annales, Series Historia et Sociologia)
In this paper I will focus on Serbian international cultural policy in relation to Croatia in the first two decades of the 21st century. Aside from giving insight into general circumstances regarding the Serbian cultural sphere after October 2000, I will discuss how tense relations between Serbian and Croatian political elites during the previous decades discouraged more extensive state-supported cultural exchange, and negatively affected the results of such initiatives. Special attention will be given to the project of joint concert seasons of the most prestigious philharmonic orchestras from Serbia, Croatia, and Slovenia titled “Pika-Točka-Tačka” (2011–2014) and its various cultural-diplomatic contributions.